A twenty year perspective on melanoma therapy - Flaherty, Keith T. (Pigment cell and melanoma research, 2023)
Melanoma had long been considered to be particularly addressable with immunotherapy, but that reputation was built on modestly effective cytokine‐based immunotherapy. CTLA‐4 antibody therapy reinforced this legacy, but PD‐1 antibodies transformed the melanoma treatment landscape and lead the way for immunotherapy to become standard treatment for more than half of the advanced cancer population. BRAF mutations were discovered in 8% of all cancer and nearly 50% of melanomas. Successful development of BRAF inhibitors and BRAF/MEK combination therapy in melanoma preceded regulatory approval across all cancer types. No cancer type saw outcomes improved by the same margin as melanoma in the decade of the 2010s. The rapid pace of progress seen from 2010 to 2014 has been followed by fewer treatments advances and smaller impact. Resistance to BRAF/MEK combination therapy and immune checkpoint antibody therapy remains to be addressed. Translational research insights suggest that new classes of therapy will be needed to make to next quantum step in patient outcomes.